Phase I, first-in-human trial of Bruton's tyrosine kinase inhibitor M7583 in patients with B-cell malignancies. Issue 10 (24th August 2021) - Jurczak, Wojciech; Rule, Simon; Townsend, William; Tucker, David; Sarholz, Barbara; Scheele, Jürgen; Dyroff, Martin; Gribben, John G.; Długosz-Danecka, Monika; Zinzani, Pier Luigi
Abstract: M7583 is a potent, highly selective, covalent BTK inhibitor in development. In this phase I, first-in-human, open label, multicenter dose-escalation trial, M7583 was given at 80 mg (three days)/160 mg (full 28-day cycle), then 300 mg/day, 600 mg/day, 900 mg/day, and 300 mg twice daily to 18 patients (median age 63 years) with refractory/resistant, stage III/IV B-cell malignancies who failed prior therapy (NCT02825836). No dose-limiting toxicities were reported. Treatment-emergent adverse events (AEs) occurred in 89% of patients, treatment-related AEs in 78%, and treatment-related grade ≥3 AEs in 17%. Common AEs were diarrhea (33%), fatigue (22%), and vomiting (17%). M7583 was rapidly absorbed and exposure was dose-proportional. BTK occupancy was >95% in the 300 mg twice daily and 900 mg/day cohorts. Objective response rate was 50% and disease control rate 78%, supporting a favorable benefit:risk profile. Fasted doses up to 900 mg once daily and 300 mg twice daily were well tolerated and may be tested in future clinical studies.